GRAMMATICAL-TRANSLATION METHOD: FOCUS ON GRAMMAR AND TRANSLATION - Komilova Zarina Komil Qizi; Shadmanov Qurban Badriddinovich (Ustozlar uchun, 2025)
The Grammatical-Translation Method (GTM) is a traditional approach to language teaching, focusing on the explicit teaching of grammar rules and vocabulary through translation exercises. This method emphasizes learning language structure and syntax through the analysis of sentence patterns and the direct translation of texts. The primary objective of GTM is to develop reading and writing skills, often at the expense of speaking and listening. Although the method has been criticized for its lack of communicative focus, it remains a useful tool in understanding complex grammatical structures and in enhancing vocabulary knowledge.